Examining the Challenges Encountered in Implementing Basic Education Strategies in Keana Local Government Area of Nasarawa State, Nigeria - Rilwan Halima Ahmed (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
Basic education remains a fundamental instrument for promoting human capital development, social transformation, and sustainable national development. Despite various educational reforms and policy interventions introduced by the Nigerian government to improve access, equity, and quality in basic education, implementation challenges continue to undermine educational outcomes, particularly at the local government level. Against this backdrop, this paper examined the challenges encountered in implementing basic education strategies in Keana Local Government Area of Nasarawa State. Specifically, the study examined the basic education strategies adopted in improving educational delivery, identified the major challenges affecting implementation, assessed the implications of these challenges on educational outcomes, and proposed measures for strengthening implementation effectiveness. The study adopted a qualitative research design and relied exclusively on secondary sources of data. Data were obtained from academic journals, textbooks, government publications, policy documents, reports of educational agencies, conference papers, and credible institutional sources relevant to basic education and policy implementation. The collected data were analysed using thematic content analysis, which enabled the identification, categorisation, and interpretation of major themes emerging from the reviewed literature and documents. The findings revealed that although several strategies such as the Universal Basic Education programme, teacher development initiatives, infrastructure expansion, and institutional reforms have contributed to improving educational access, implementation remains constrained by inadequate funding, shortage of qualified teachers, poor infrastructure, weak institutional coordination, ineffective monitoring mechanisms, and low community participation. The study further found that these implementation challenges negatively affect enrolment, educational quality, student performance, and overall policy effectiveness. The paper concludes that effective implementation of basic education strategies requires more than policy formulation and demands sustained investment, institutional strengthening, and collaborative stakeholder engagement. The study recommends increased funding for education, improved teacher recruitment and capacity development, stronger monitoring and evaluation systems, enhanced institutional coordination, and greater community participation to improve educational outcomes in Keana Local Government Area.